# Write the following equation in the general form ax+ by +c = 0. y - x - 1 = 0

**Solution:**

Given y - x - 1 = 0

General form of a straight line ax +by+c =0

First the x term should be placed, then y term and at last the constant term.

Here, the coefficient of x is -1, the coefficient of y is 1, the constant is 1.

Rewriting the equation y - x - 1 = 0

⇒ -1x + 1y +(-1) =0, which is in the general form ax + by + c =0

## Write the following equation in the general form ax+ by +c = 0. y - x - 1 = 0

**Summary: **

The following equation in the general form ax + by + c = 0. y - x - 1 = 0.The general form of y-x-1=0 is -1x + 1y +(-1) =0.

Math worksheets and

visual curriculum

visual curriculum